2020
DOI: 10.1002/ijgo.13249
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of COVID‐19 quarantine measures in northeastern Italy on mothers in the immediate postpartum period

Abstract: Objective To explore whether quarantine measures and hospital containment policies among women giving birth in a COVID‐19 “hotspot” area in northeastern Italy enhanced psycho‐emotional distress in the immediate postpartum period. Methods We designed a non‐concurrent case–control study of mothers who gave birth during a COVID‐19 quarantine period between March 8 and May 3, 2020 (COVID‐19 study group), with an antecedent group of matched postpartum women (control group) who delivered in the same period in 2019. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
281
4
12

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(315 citation statements)
references
References 22 publications
18
281
4
12
Order By: Relevance
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The present study ndings show that the prevalence of postpartum depressive and post-traumatic stress symptoms among the women experiencing childbirth during the Covid-19 pandemic was higher than that reported in previous studies before the pandemic. Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36].…”
Section: Discussionsupporting
confidence: 50%
“…Literature data report that approximately 10-16% of women met major depression's criteria at 3 months postpartum [24,[33][34][35][36]. The ndings for our cohort (30.7%) are shared by a recent study that reported that 30% of the mothers who delivered during the Covid-19 pandemic had a global EPDS score > 12 compared with 11.9% in an antecedent matched group of postpartum women [36]. An EPDS score > 13 was self-identi ed by another online survey in 15% of women before and in 40.7% during the outbreak for the same cohort of women who were pregnant or within the rst year after delivery [35].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our results point towards an increased likelihood of depressive symptoms and anxiety among pregnant women and women in the early postpartum period during the COVID‐19 lockdown, thereby corroborating previous findings 4 . Obstetricians and policymakers should be aware that COVID‐19, along with its isolation measures, may put a high(er) burden on the emotional wellbeing of pregnant women and women in the early postpartum period.…”
Section: Pregnant Women Breastfeeding Women N % Mean (±Sd) N % Mean (mentioning
confidence: 63%
“…Importantly, the distinction between our method of universally screening all postpartum patients and previous studies exploring maternal mood during the COVID-19 pandemic (25-28) likely explains, at least in part, the differences in our ndings compared to theirs. That is, they not only did not differentiate between SES, but in addition likely suffered from well understood methodological limitations associated with sampling bias in choosing only to study individuals who independently responded to social media announcements (25,26), anonymously e-mailed online survey requests (27) or other voluntary participation requests (28). Second, we were unable to analyze the data for demographic differences beyond SES.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced pollution levels, a decline in the rates of automobile accidents, and a lower incidence of non-COVID infectious disease (24) all appear secondary to imposed social, educational and employment restrictions. Unsurprisingly, early explorations into the impact of the COVID-19 pandemic on maternal populations have reported increases in anxiety and depression (25)(26)(27)(28). While these ndings represent valuable contributions to the literature, the majority of these studies have suffered from important methodological limitations, including relying solely on self-selection recruitment methods, such as social media advertisements (25,26) and e-mailed online surveys (27) that are prone to biased sampling, may directly in uence outcome measures, and are well understood threats to the generalizability of the ndings.…”
Section: Introductionmentioning
confidence: 99%